Cash Richness and Propensity to Acquire –An Empirical Examination Based on Largest Deals - Kumar, Rajesh; Oberoi, Sarbjit Singh (International Journal of Economics and Financial Issues, 2019)
The study aims to examine if cash rich firms become acquirers. The study was based on the largest 100 deals completed in the year 2017. The sample deal was selected among the 9000 deals in the year 2017. The source of data was Thomson Reuters. Firms were classified into cash rich and cash poor based on a baseline model. Six binary logistic regression models were used to examine the likelihood of a firm becoming an acquirer. The results suggest that higher the cash intensity, greater is the probability of firms becoming acquirer firms. In other words, cash rich firms tend to become acquirers. Higher the leverage, greater the propensity of firms to become acquirer. Lower EPS for firms have higher acquisition likelihood. Keywords: Debt Repayment, Mergers and Acquisitions, Capital Investments, Cash reserves, Corporate Restructuring JEL Classifications: G30; G34 DOI: https://doi.org/10.32479/ijefi.7867